2019
DOI: 10.1083/jcb.201812073
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of GEF-H1 activation controlled by microtubule- and Src-mediated pathways

Abstract: Rho family GTPases are activated with precise spatiotemporal control by guanine nucleotide exchange factors (GEFs). Guanine exchange factor H1 (GEF-H1), a RhoA activator, is thought to act as an integrator of microtubule (MT) and actin dynamics in diverse cell functions. Here we identify a GEF-H1 autoinhibitory sequence and exploit it to produce an activation biosensor to quantitatively probe the relationship between GEF-H1 conformational change, RhoA activity, and edge motion in migrating cells with micromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…GEF-H1 is the only Rho-GEF known to be negatively regulated by microtubule binding. [33][34][35] We therefore analyzed effects of the mi-…”
Section: Pka and Pkg Phosphorylate Gef-h1 On S886 Increasing 14-3-3mentioning
confidence: 99%
“…GEF-H1 is the only Rho-GEF known to be negatively regulated by microtubule binding. [33][34][35] We therefore analyzed effects of the mi-…”
Section: Pka and Pkg Phosphorylate Gef-h1 On S886 Increasing 14-3-3mentioning
confidence: 99%
“…An excellent approach is the use of optogenetics to reversibly trigger signaling with spatial and temporal control in the subsecond range [176,177]. Such light-sensitive tools have already been successfully developed to control the activity of endogenous Rho GTPases in various settings [178][179][180] and can easily be combined with genetically encoded biosensors for monitoring local Rho GTPase or RhoGEF activity [47,62,64].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, GEF-H1 also promotes the fission of carriers at the trans-Golgi network [46]. In motile cells, GEF-H1 activity is controlled by phosphorylation through the protein tyrosine kinase c-Src, and this is critical for RhoA activation at the leading edge [47]. However, GEF-H1 is also implicated in the endosomal trafficking of c-Src [44].…”
Section: Spatiotemporal Rho Regulation By Gefs and Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that Src signaling could regulate the expression and activity of GEF proteins (Scott et al, 2016;Azoitei et al, 2019). To exploit the relationship between Src signaling pathway members, we examined the roles of P115-RhoGEF/ROCK and GEF-H1/ROCK signaling in CX3CL1stimulated VMECs.…”
Section: Cx3cl1 Induces Src/p115-rhogef/rock Signaling Activation In mentioning
confidence: 99%